2007
DOI: 10.3748/wjg.v13.i19.2669
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression arrays as a tool to unravel mechanisms of normal tissue radiation injury and prediction of response

Abstract: Over the past 5 years there has been a rapid increase in the use of microarray technology in the field of cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Currently, much work is focused on the use of microarray technology as a way to generate genetic signature profiles which will indicate the probable response of a tumour to radiation [reviewed in (21)]; this approach represents promising and revolutionary technology. However, the implementation of this technology in predictive radiation biology has yet to be validated and there are still some important limitations with regards to interpretation of gene expression data, complications raised by cell heterogeneity and expense.…”
Section: Prediction Of Tumour Radiosensitivitymentioning
confidence: 99%
“…Currently, much work is focused on the use of microarray technology as a way to generate genetic signature profiles which will indicate the probable response of a tumour to radiation [reviewed in (21)]; this approach represents promising and revolutionary technology. However, the implementation of this technology in predictive radiation biology has yet to be validated and there are still some important limitations with regards to interpretation of gene expression data, complications raised by cell heterogeneity and expense.…”
Section: Prediction Of Tumour Radiosensitivitymentioning
confidence: 99%
“…Using subcutaneous fibroblasts from breast cancer patients, Rodningen et al (2007) identified a set of 18 radiation-responsive genes, which may provide a predictive assay for late normal tissue reactions after radiotherapy. The amount of information available on gene expression responses to radiation has been increasing considerably in recent years (Kruse and Stewart, 2007). These studies of altered gene expression have been useful for elucidating the molecular mechanisms underlying cellular radiation response and a few have been able to identify genes as potential indicators of severe reactions to radiotherapy treatment.…”
mentioning
confidence: 99%
“…An example to this is the study from Ichimura et al who identified the gene with most significant change in the postischemic rat kidney, KIM-1, and confirmed its viability for use as a biomarker by subsequent immunoblot, immunostaining, and RNA in situ hybridization [9]. Examples to other similar studies in which analysis of microarray data is used to find markers and changed gene expression levels for damage due to radiation toxicity [11], hemolytic anemia induced by drugs [12], nephrotoxicity induced by cisplatin [13], identification of glutathione depletion-responsive genes in rat liver [14], and many more. This approach is powerful, and pharmaceutical and biotechnology companies even created panels of biomarkers that detect drugs causing hepatotoxicity upon in vitro exposure to rat hepatocytes or in vivo dosing in rats [15].…”
Section: Related Workmentioning
confidence: 97%